ANALISIS KELAYAKAN USAHATANI CABAI MERAH DI LAHAN GAMBUT KOTA PALANGKA RAYA KALIMANTAN TENGAH (The Feasibility Of Red Chili Farming In Peatlands Of Palangka Raya In Central Kalimantan) - journal, journal (AgriPeat, 2017)
ABSTRACT Red chili becomes one of commodity contributor to inflation in Central Kalimantan. This is because the price of chili that continues to rise and tend to be unstable, and its supply is still dependent from outside Central Kalimantan.Red chili cultivation has not been developed in peatlands. Palangka Raya has peatland potential for the development of red chilicultivation. The assessment aims to get the feasibility of red chili farming in peatlands of Palangka Raya in Central Kalimantan. The assessment conducted in the PetukKatimpun Villages, District Jekan Raya in June to November 2014, with the planting on the farmer’s land cooperators 0.25 hectares. The technology cultivation adopted from Indonesian Vegetable Research Institute (Balitsa) which has been modified. Pillar varieties used are favored by the market because of its shape. Giving fertilizer used manure 20 t/ha, NPK 16:16:16 1 t/ha, dolomite 2 t/ha, limestone 1 t/ha, calcium boron 14 liter/ha. The assessment results obtained production of red chili 16,743 t/ha. The value of R/C ratio of 5.89 and B/C 4.89 so red chili farming in the peatlands feasible to develop and profitably. Keywords: Red Chili, Peatlands, Feasibility Analysis ABSTRAK Cabai merah menjadi salah satu komoditas penyumbang inflasi di Kalimantan Tengah. Hal ini dikarenakan harga cabai yang terus naik, cenderung tidak stabil serta pasokan yang masih tergantung dari luar Kalimantan Tengah. Budidaya cabai merah juga belum banyak dikembangkan di lahan gambut. Kota Palangka Raya mempunyai lahan gambut yang potensial untuk pengembangan budidaya cabai merah. Pengkajian ini bertujuan untuk mendapatkan hasil kelayakan usaha tani cabai merah di lahan gambut Kota Palangka Raya Kalimantan Tengah. Pengkajian ini dilaksanakan di Desa Petuk Katimpun Kecamatan Jekan Raya pada Juni sampai Nopember 2014 dengan melakukan penanaman dilahan petani kooperator seluas 0,25 ha. Teknologi budidaya diadopsi dari Balai Penelitian Tanaman Sayuran (Balitsa) yang telah dimodifikasi. Varietas yang digunakan adalah Pilar karena bentuknya disukai oleh pasar. Pemberian pemupukan menggunakan pupuk kandang 20 t/ha, NPK 16 : 16 : 16 1 t/ha, dolomite 2 t/ha, kapur bangunan 1 t/ha, calcium boron 14 liter/ha. Hasil pengkajian didapatkan produksi cabaimerah 16,743 t/ha. Nilai R/C ratio sebesar 5.89 dan B/C 4.89 sehingga usaha tani cabaimerah di lahan gambut layak untuk dikembangkan dan menguntungkan. Kata Kunci: Cabai Merah, Lahan Gambut, Analisis Kelayakan